Education Activism in the Trump-DeVos Era: Opt Out Florida's Leaders Respond to the 2016 Election. Issue 1 (2nd January 2021) - Schroeder, Stephanie; Currin, Elizabeth; McCardle, Todd
Abstract: This paper investigates the impact of the 2016 presidential election on the Opt Out Florida Network (OOFN). Findings indicate that the widespread protests against the Trump presidency after the election highlighted the need to reframe OOFN's message in order to motivate membership to act for democratic schools. We suggest the outcome of OOFN's protest largely depends on the resonance of OOFN's framing tactics with the larger public and their own membership.